The Effect of Organizational Commitment, the Effectiveness of Internal Controls, Law Enforcement, Love of Money, and Information Asymetries on Fraud (Empirical Study on SKPD of North Aceh Regency Government) - Darwanis Darwanis; Fifi Yusmita; Teuku Meurah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to examine the effect of organizational commitment, effectiveness of internal control, law enforcement, love of money, and information asymmetry on fraud at SKPD of the North Aceh Regency Government. The population of this research is all units of SKPD the North Aceh Regency which totaling 60 SKPD (180 respondents).The qualified respondents consist of 180 respondents. Data collection techniques were conducted with questionnaires. The results of this research shown that simultaneously and partially, organizational commitment, effectiveness of internal control, law enforcement, love of money, and information asymmetry affect on fraud at SKPD of the North Aceh Regency Government.